Super edge-magic total labeling on w-trees - Javaid M.; Hussain M.; Ali K.; Dar K.H. (Utilitas Mathematica, 2011)
An edge-magic total labeling of a graph G is a one-toone map A from V(G) U E(G) onto the integers 1,2, ..., |V(G) U E(G)} with the property that, there is an integer constant c such that λ(x) + λ(x, y) + λ(y) = c for any (x, y) ⋯ E(G). If λ(V(G)) = 1,2, ...| V(G| then edge-magic total labeling is called super edgemagic total labeling. In this paper we formulate super edge-magic total labeling on w-trees.